The ANALYSIS Of THE QUALITY INFLUENCING FACTORS Of REGIONAL GOVERNMENT FINANCIAL REPORTS And THE IMPLICATION TOWARDS THE GOVERNMENT EMPLOYEE PERFORMANCE Of LAMPUNG PROVINCE GOVERNMENT - Lestari, Raisa (FEB - Universitas Lampung, 2021)
This study aims to examine the relationship between the influence of human resource capacity, the application of government internal control systems and the use of information technology to the quality of local government financial reports, and their implications for employee performance. The study was conducted among 107 employees who worked in the accounting department of the Regional Agency for Financial Management and Assets and the Regional Revenue and Asset Management Service, who had responsibilities and main functions in the preparation of financial reports of district governments of Lampung Province. The data analysis technique used in this study is the SEM (Structural Equation Model) method using the AMOS program as a research tool. This research shows empirical evidence that human resource capacity, the application of government internal control systems and the use of information technology have a positive effect on the quality of local government financial reporting, this study found. also successfully demonstrated that there is a positive influence on the quality of local government financial statements on employee performance.